COMPLIANCE DIET INPATIENT DIABETES MELLITUS BASED ON THEORY COMPLIANCE BY NIVEN - Ilmah, Farida; Rochmah, Thinni Nurul (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTÂ Diabetes Mellitus is one of disease related to nutrition. Diabetes Mellitusinpatientâs food waste plate is one of the manifestation of noncompliance to the diet program that have been recommended by health workers. This study analyzed the influence of noncompliance inpatients with Diabetes Mellitus diet in dr. M. Soewandhie Surabaya based on the theory compliance by Niven. This was analytic observasionalstudy with cross sectional design. This study used32 samples. Data were analyzed using linear regression test. The results showed that 64.7% of respondents who have a good attitude did notcomply to the diet, 85,7% of respondentswho noncompliance to the diet has very good belief. Meanwhile, 50% of respondents who di not understand the instruction from nutritionists belonging to noncompliance. Then 85.7% of respondents felt lack of support from their family classified as noncompliance category. While, 75% of respondents who feel very good quality interaction with nutritionists belonging to noncompliance respondent. While, 66,7% respondents who got enough support from nutritioniststned to comply the diet. The study showed that official support (nutritionists) influence the patient compliance (Ï = 0,000) with a value of B = -6. Counseling to inpatients Diabetes Mellitus diet every daycould change the compliance patients.Â Keywords: compliancetheory, DiabetesÂ  mellitus diet, food waste plate, health Â  Â  Â  Â  Â  Â  Â  Â  worker support, niven